2010
DOI: 10.1590/s0100-40422010000200020
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and emergency admissions for cardiorespiratory diseases in Lisbon (Portugal)

Abstract: Recebido em 6/3/09; aceito em 30/7/09; publicado na web em 11/1/10 AIR POLLUTION AND EMERGENCY ADMISSIONS FOR CARDIORESPIRATORY DISEASES IN LISBON (PORTUGAL).Daily records of hospital admissions due to cardiorespiratory diseases and levels of PM 10 , SO 2 , CO, NO, NO 2 , and O 3 were collected from 1999-2004 to evaluate the relationship between air pollution and morbidity in Lisbon. Generalised additive Poisson regression models were adopted, controlling for temperature, humidity, and both short and long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 77 publications
(71 reference statements)
1
35
0
Order By: Relevance
“…In contrast, [49] found that elevated PM 10 levels indicate a dominant role among the main air pollutants. [30,61] found that the association between particulate matter and health conditions was not significant, while others [38,60,64,[66][67][68][69][70][71] found that the number of admissions for respiratory causes rose significantly with increased exposure to particulate matter. It should be added that the health impact of particulates is complex as their biological effect can be influenced by the particle size and composition [30].…”
Section: Season Ofmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, [49] found that elevated PM 10 levels indicate a dominant role among the main air pollutants. [30,61] found that the association between particulate matter and health conditions was not significant, while others [38,60,64,[66][67][68][69][70][71] found that the number of admissions for respiratory causes rose significantly with increased exposure to particulate matter. It should be added that the health impact of particulates is complex as their biological effect can be influenced by the particle size and composition [30].…”
Section: Season Ofmentioning
confidence: 99%
“…They include the daily average mass concentrations of CO (mg . m-3 ), NO, NO2, SO 2 , O 3 and PM 10 (µg⋅m-3 ) [30]. When selecting biological air pollutants special emphasis is put on Ambrosia due to its above mentioned characteristics in Hungary.…”
Section: Location and Datamentioning
confidence: 99%
See 3 more Smart Citations